Iatrogenic postoperative cerebellar cyst. (December 2016) - Sharif, Robin; Moscovici, Samuel; Wygoda, Marc; Eliahou, Ruth; Spektor, Sergey
Highlights: An iatrogenic cerebellar cyst developed after retrosigmoid craniotomy. The patient had previously undergone stereotactic radiosurgery for vestibular schwannoma. We hypothesize the cyst formed from a small arachnoid or parenchymal tear. The water hammer effect of cerebrospinal fluid pulsatility may have caused cyst formation. A small corticectomy of the cerebellum provided communication to the cistern magna. Abstract: Cerebellar cyst is a known but uncommon entity. It is congenital in most cases, or may develop after brain parenchyma injuries or interventions. To our knowledge, de novo cerebellar cyst after extra-axial tumor excision, has not been described in the literature. We present the first reported case of a de novo cerebellar cyst developing in a 70-year-old woman following retrosigmoid craniotomy for vestibular schwannoma excision, and discuss the possible causes. Following cyst fenestration, there was no clinical or radiological evidence of a residual cyst.